Recombinant porcine factor VIII for high‐risk surgery in paediatric congenital haemophilia A with high‐titre inhibitor. Issue 2 (25th January 2017) - Croteau, S. E.; Abajas, Y. L.; Wolberg, A. S.; Nielsen, B. I.; Marx, G. R.; Baird, C. W.; Neufeld, E. J.; Monahan, P. E.
Abstract : Introduction: High‐titre factor VIII (FVIII) inhibitors complicate peri‐operative haemostasis. Recombinant porcine FVIII (r‐pFVIII) may provide an alternative haemostatic agent for high‐risk procedures and allow FVIII activity monitoring. Aim: Devise an effective haemostatic plan for repair of a progressively symptomatic aortic coarctation in a 5‐year‐old male with immune tolerance induction (ITI) refractory high‐titre FVIII inhibitors. Methods: Preprocedure human FVIII inhibitor titre was 58 Bethesda Units mL −1 (BU) and cross‐reacted to neutralize porcine FVIII at 30 BU. Daily ITI with plasma‐derived FVIII concentrate was supplemented with anti‐B‐cell and anti‐plasma cell immunotherapy to reduce FVIII inhibitor titres. Potential haemostatic agents were evaluated in comparative ex vivo thrombin generation assays (TGA). Results: Four weeks after immunosuppression, human and porcine inhibitor titres declined to 16 and 2 BU respectively. TGA with r‐pFVIII was less robust than with activated prothrombin complex concentrate (aPCC); however, r‐pFVIII was selected for cardiac surgery to secure the ability to assay FVIII levels throughout this high‐bleeding risk procedure. Haemostasis with r‐pFVIII was excellent; initial trough FVIII activity levels ranged from 0.81–1.17 IU mL −1 . On postoperative day 3, peak and trough levels markedly declined suggesting a rising porcine inhibitor titre. Postprocedure prophylaxis was transitioned to aPCC, informed by TGA. Conclusions: R‐pFVIII provided effective peri‐procedural haemostasis with no adverse events. Rapid neutralization of r‐pFVIII after the first 60 hours, despite intensive immune suppression, accentuates the importance of careful monitoring. Use of TGA can support bypassing agent selection for convalescence. The comparative cost of r‐pFVIII may limit its use to high morbidity clinical scenarios.